2008
DOI: 10.1016/j.amepre.2007.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Neighborhood Resources in High School Girls

Abstract: Background-Physical activity behavior is influenced by a person's physical environment, but few studies have used objective measures to study the influences of the physical environment on physical activity behavior in youth. The purpose of this study was to examine the relationship between selected neighborhood physical activity resources and physical activity levels in high school girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 32 publications
3
50
2
2
Order By: Relevance
“…Self-efficacy for overcoming barriers to physical activity accounted for the crosssectional relation between physical activity and girls' perceptions of environmental access in the 9th [15] and the 12th grades [16] and accounted for part of the relation between perceived social support and physical activity in the 12th grade. In another LEAP study using GIS technology, the number of 30-min blocks of vigorous physical activity (VPA) was associated with proximity to the total number of commercial PA facilities (individual, multipurpose, and team facilities) within 0.75-mile street network buffer of the homes of 1,234 12th grade girls [17].…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy for overcoming barriers to physical activity accounted for the crosssectional relation between physical activity and girls' perceptions of environmental access in the 9th [15] and the 12th grades [16] and accounted for part of the relation between perceived social support and physical activity in the 12th grade. In another LEAP study using GIS technology, the number of 30-min blocks of vigorous physical activity (VPA) was associated with proximity to the total number of commercial PA facilities (individual, multipurpose, and team facilities) within 0.75-mile street network buffer of the homes of 1,234 12th grade girls [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, some research has demonstrated that adolescents living in neighbourhoods with sites and equipment available for physical activity were physically more active 39,40 . Systematic reviews have demonstrated an inconsistent relationship between physical activity level and environment characteristics in adolescents 10,15,16 .…”
Section: Variablesmentioning
confidence: 99%
“…Likewise, the use of GIS to create circular buffers centred on residents' homes has been used elsewhere to study the associations between local contextual conditions and health outcome (Chaix et al, 2005a;Chaix et al, 2005b;Chaix et al, 2006). Buffers can be used to obtain summary measures of local factors which can then be examined in relation to the health outcome of interest, with the size of these circular surfaces (e.g., a given radius around each residential address) being based on the study's purpose (Berke et al, 2007;Crawford et al, 2008;Pate et al, 2008). For IDUs as well as the average resident, a 10-minute walking distance, corresponding to a 500-meter buffer, is generally recognised as a reasonable radius by which to represent access to local services.…”
Section: Introductionmentioning
confidence: 99%